A COMPOSITE INDEX-BASED ASSESSMENT OF ECONOMIC GROWTH QUALITY IN DA NANG CITY DURING THE PERIOD 2015–2023 - Van Canh, Truong (Tạp chí Khoa học Trường Đại học Sư phạm Hà Nội: Khoa học Xã hội, 2025)
Amid growing emphasis on sustainable development, evaluating the quality of economic growth has become a vital priority for local governments. This study proposes a multi-dimensional evaluation framework and a composite index to assess the quality of economic growth in Da Nang City from 2015 to 2023. The study applies 29 indicators grouped into four key dimensions - economic efficiency, social welfare, environment and security, and governance capacity - and employs the FPPSI method (Full Permutation Polygon Synthetic Indicator) to normalize indicators and construct the composite index. The findings reveal that the quality of Da Nang’s economic growth remains moderate, with the composite index ranging from 0.43 to 0.45 during the period 2015-2023. Among the dimensions, social welfare exhibited the most notable improvement, reaching a good level in 2023 (0.71), followed by environment and security (0.55). In contrast, economic efficiency recorded the weakest performance, with a steep decline during the COVID-19 period (0.10 in 2021) and only a partial recovery by 2023 (0.24). Governance capacity showed minimal fluctuation, staying consistently below the good threshold (0.31). These findings highlight the need for Da Nang to enhance economic efficiency, environmental protection, and strengthen governance systems to improve the quality of its economic growth toward long-term sustainability.